A Review of Flow Migration Through Mobile Networks - Alqaysi, Manhal K.; Behadili, Suhad Faisal (Iraqi Journal of Science, 2022)
The interesting new sources of data for official statistics are cell phone data. Electronic media has defined the way of research human behavior rapidly over the last decade. As data storage and sensing technology progressed, electronic records now cover a diverse variety of human activities from localized data (phone) to open source contributions on Wikipedia and the Open Area Map. Electronic records now encompass the numerous fields of activity. The ad hoc vehicle network is a research community-based wireless technology for the implementation of intelligent transport applications. It is necessary to estimate migration flows and predict future trends to understand the causes and effects of migration and to enforce policies to deliver certain services. Several studies have exposed in this review with their datasets such as Credit card records (CCRs) provide deep insight into buying behavior; Call Details Records (CDRs) present new possibilities for under-implemented human mobility. Therefore, various forms of transportation and other travel behavior, various travel-related events such as "Home-Tour-Work -Tour-Tour” and the corresponding travel-related motifs have also been distinguished by the inclusion of land use details in the GIS data. This review also investigated migration trips residence between cities and inside a single city. The review concluded clear results for the adoption of the mentioned data, for example, mobile phone data (CDRs), because it is very useful as it provides real big data or real time big data without additional cost and is available in telecommunications companies, from which it is possible to analyze the movement of communities and deduce the activity of a particular city. In the future, there is a tendency to use this type of data from Korek Telecom Company in Iraq to the flow migration of Iraq governorates by using the gravity model. As well as, an attempt to study the conditions of cities and the movement of individuals in urban places to clarify the needs of the city in its need for new improvements.